A Near-Infrared, Wavelength-Shiftable, Turn-on Fluorescent Probe for the Detection and Imaging of Cancer Tumor Cells - Shen, Zhenhua (ACS Chem Biol, 2017)
Fast, selective, and noninvasive reporting of intracellular cancer-associated events and species will lead to a better understanding of tumorigenesis at the molecular level and development of precision medicine approaches in oncology. Overexpressed reductase presence in solid tumor cells is key to cancer progression and protection of those diseased cells from the oxidative effects of therapeutics meant to kill them. Human NAD(P)H:quinone oxidoreductase isozyme I (hNQO1), a cytoprotective 2-electron-specific reductase found at unusually high activity levels in cancer cells of multiple origins, has attracted significant attention due to its major role in metastatic pathways and its link to low survival rates in patients, as well as its ability to effectively activate quinone-based, anticancer drugs. Accurate assessment of hNQO1 activities in living tumor models and ready differentiation of metastases from healthy tissue by fluorescent light-based protocols requires creation of hNQO1-responsive, near-infrared probes that offer deep tissue penetration and low background fluorescence. Herein, we disclose a quinone-trigger-based, near-infrared probe whose fluorescence is effectively turned on several hundred-fold through highly selective reduction of the quinone trigger group by hNQO1, with unprecedented, catalytically efficient formation of a fluorescent reporter. hNQO1 activity-specific production of a fluorescence signal in two-dimensional cultures of respiring human cancer cells that harbor the reductase enzyme allows for their quick (30 min) high-integrity recognition. The characteristics of the near-infrared probe make possible the imaging of clinically relevant three-dimensional colorectal tumor models possessing spatially heterogeneous hNQO1 activities and provide for fluorescence-assisted identification of submillimeter dimension metastases in a preclinical mouse model of human ovarian serous adenocarcinoma.